Effect of Different Mulches on Growth and Yield of Cauliflower in Southern Bangladesh - Sil, MC; Haque, MZ; Shila, A; Howlader, MHK; Ahmed, R (Journal of Environmental Science and Natural Resources, 2022)
A field experiment was conducted at the research farm of Patuakhali Science and Technology University (PSTU), Patuakhali from November 2011 to April 2012 to find out the most adventitious mulch material for Cauliflower production. The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications. Six different mulches (M) along with control were applied as treatment viz M0 =Control (without mulches), M1 =Black polythene, M2 =White polythene, M3 =Saw dust, M4 =Water hyacinth and M5 =Rice straw. Data were compared on plant height (cm); number of leaves/plant; leaf area (cm2)/plant; leaf area index (cm2); dry weight of root, leaf and stem (g/plant); total dry matter (g/plant); crop growth rate (g/m2/day); relative growth rate (g/cm2/day); diameter of curd (cm2); curd fresh weight (g/plant) and curd yield (t/ha). Significant variation was obtained in case of all the compared parameters among the treatments but water hyacinth mulch gave highest value compared to control and other mulches. Finally, it can be concluded that water hyacinth mulch was found most effective for cauliflower production under AEZ-13 of the southern part of Bangladesh. Environ. Sci. & Natural Resources, 13(1&2): 110-117, 2020